Estimating the Prevalence of Asymptomatic COVID-19 Cases and Their Contribution in Transmission - Using Henan Province, China, as an Example - Li, Chunyu; Zhu, Yuchen; Qi, Chang; Liu, Lili; Zhang, Dandan; Wang, Xu; She, Kaili; Jia, Yan; Liu, Tingxuan; He, Daihai; Xiong, Momiao; Li, Xiujun (Frontiers in Medicine, 2021)
Background: A novel coronavirus disease 2019 (COVID-19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), is now sweeping the world. A substantial proportion of infections only lead to mild symptoms or are asymptomatic, but the proportion and infectivity of asymptomatic infections remained unknown. In this paper, we proposed a model to estimate the proportion and infectivity of asymptomatic cases, using COVID-19 in Henan province, China as an example. Methods: We extended the conventional susceptible-exposed-infectious-recovered model by including asymptomatic, unconfirmed symptomatic and quarantined cases. Based on this model, we used daily reported COVID-19 cases from January 21 to February 26, 2020 in Henan province to estimate the proportion and infectivity of asymptomatic cases, as well as the change of effective reproductive number, R_t. Results: The proportion of asymptomatic cases among COVID-19 infected individuals was 42% and the infectivity was 10% of that symptomatic ones. The basic reproductive number R_0=2.73, and R_t dropped below 1 on January 31 under a series of measures. Conclusion: The spread of COVID-19 epidemic was rapid in the early stage, with a large number of asymptomatic infected individuals having relatively low infectivity. However, it was quickly brought under control with national measures.